« Un néant follement attifé » : macabre et grotesque dans Mesure pour Mesure - Sophie Chiari (Sillages Critiques)
In an anamorphic play such as Measure for Measure, the grotesque is endowed with a strong satirical power, and its close relation to the macabre makes it even stronger. Shakespeare actually depicts a dramatic vanitas and places the morbid at the heart of Vienna, regarded as a world marked by confinement and instability. In this town infested by the syphilis and threatened by the plague, Claudio, Juliet, Isabella, Mariana, Angelo and the Duke are described as doppelgängers haunted by the same quest for absolutes and the same luxuriousness. Thus, the play presents us with a whole series of frail and disquieting characters, and the medieval theme of the Dance of Death running throughout the tragicomedy reveals the vanity of their speeches and attitudes. Therefore, beyond its festive characteristics, the Shakespearean grotesque is particularly dark, and it underlines flaws whose tragic dimension will be clearly seen in a play like King Lear.